Modeling and computational simulation in a production line of a company in the clothing segment located in Telêmaco Borba-PR - Sousa, Vitor Gabriel Santos; Barreto, Gustavo Szmoski; dos Santos Filho, Vitor Hugo (Brazilian Journal of Production Engineering, 2024)
The overarching goal is to model and simulate a production line of a clothing company located in Telêmaco Borba – PR, with the aim of proposing enhancements to production capacity. The research method encompasses conception stages, involving the creation of a conceptual model, implementation stages, encompassing scenario creation, and analysis stages. Scenario 1 proposed the removal of distribution and return to the company, along with the hiring of one employee. Scenario 2 suggested eliminating distribution and return processes and employing two operators who could operate all three machines simultaneously. The third and final scenario also involved eliminating distribution and return processes and hiring three employees, allowing for the simultaneous operation of the three machines and the addition of a machine to the sewing and finishing process. Through the analysis of data obtained from simulations, it was concluded that the optimal scenario for the company is scenario 3, as it demonstrated an 8.67% increase in production capacity.